Sistem Informasi Distribusi Salker dan Alker untuk Manajemen Rantai Pasokan dengan Rapid Application Development (RAD) - Manikam, Ratna Mutu; Wibisana, Pandu (FORMAT, 2024)
This research develops the Alker and Salker distribution information system for supply chain management using the Rapid Application Development (RAD) method. This system aims to overcome the problem of monitoring stock in area and central warehouses, as well as improving the efficiency of goods distribution from the center to the area. In this research, observation, interviews and literature study methods were used to collect data, while Fishbone diagrams were used to analyze problems. The application development process involves several stages, starting from requirements planning, design workshops, to system implementation and testing. This system is designed using UML to describe use cases and activity diagrams, and is equipped with an intuitive user interface. System testing is carried out using the White Box method, which tests various logic paths in the application to ensure that no errors occur. The research results show that the application developed is able to increase the efficiency of supply chain management by providing accurate stock information and facilitating the management of transactions between warehouses. With this system, companies can minimize errors in stock management and ensure the distribution of goods runs smoothly. The implementation of this system is expected to increase the company's operational productivity and efficiency, especially in the management of Alker and Salker. This research contributes to the literature regarding the use of RAD in the development of supply chain information systems and provides practical solutions to goods distribution problems in companies.. Keywords : Supply Chain Management; Rapid Application Development (RAD); JavaScript; MySQL Abstrak   Penelitian ini mengembangkan sistem informasi distribusi Alker dan Salker untuk manajemen rantai pasokan menggunakan metode Rapid Application Development (RAD). Sistem ini bertujuan untuk mengatasi masalah pemantauan stok di gudang area dan pusat, serta memperbaiki efisiensi distribusi barang dari pusat ke area. Dalam penelitian ini, metode observasi, wawancara, dan studi pustaka digunakan untuk mengumpulkan data, sementara diagram Fishbone digunakan untuk menganalisis permasalahan. Proses pengembangan aplikasi melibatkan beberapa tahapan, mulai dari perencanaan kebutuhan, workshop desain, hingga implementasi dan uji coba sistem. Sistem ini dirancang menggunakan UML untuk menggambarkan use case dan activity diagram, serta dilengkapi dengan antarmuka pengguna yang intuitif. Pengujian sistem dilakukan menggunakan metode White Box, yang menguji berbagai jalur logika dalam aplikasi untuk memastikan tidak ada kesalahan yang terjadi. Hasil penelitian menunjukkan bahwa aplikasi yang dikembangkan mampu meningkatkan efisiensi manajemen rantai pasokan dengan menyediakan informasi stok yang akurat dan memfasilitasi pengelolaan transaksi antar gudang. Dengan sistem ini, perusahaan dapat meminimalkan kesalahan dalam pengelolaan stok dan memastikan distribusi barang berjalan dengan lancar. Implementasi sistem ini diharapkan dapat meningkatkan produktivitas dan efisiensi operasional perusahaan, khususnya dalam pengelolaan Alker dan Salker. Penelitian ini berkontribusi pada literatur mengenai penggunaan RAD dalam pengembangan sistem informasi rantai pasokan dan memberikan solusi praktis untuk masalah distribusi barang di perusahaan. Keywords : Supply Chain Management; Rapid Application Development (RAD)